KAMPANYE PENINGKATAN PENGETAHUAN MAHASISWA TERHADAP BUS WISATA KOTA SEMARANG SEBAGAI STRESS RELIEF - Keysha Alya Witjaksono; Yohanes Thianika Budiarsa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The high level of stress experienced by university students due to academic demands highlights theneed for accessible and engaging stress relief alternatives. Bus Wisata Kota Semarang, a cityprovidedtourism transportation service, has the potential to function as both a recreational andeducational medium by offering a unique city tour experience across iconic destinations; however,students’ awareness and knowledge of this service remain relatively low, limiting its utilizationamong the target audience. This study aims to analyze the implementation of a communicationcampaign designed to increase students’ knowledge and interest in using Bus Wisata Kota Semarangas a stress relief alternative. The campaign employed integrated communication strategies, includingCyber Public Relations, Advertising, Event and Experiences, and Key Opinion Leaders, supportedby the AISAS (Attention, Interest, Search, Action, Share) model to guide audience behavior. Datawere collected through pre- and post-campaign surveys, database tracking, and campaignmonitoring. The results show a significant increase in students’ knowledge from 20% to 87.6%, alongwith the successful collection of 537 student databases, indicating improved awareness, knowledge,and overall campaign effectiveness in combining digital and experiential approaches.